2014
DOI: 10.1002/ange.201408124
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Stability of a Lithium‐Ion‐Conducting Solid Electrolyte upon Reversible Li+/H+ Exchange in Aqueous Solutions

Abstract: Batteries with an aqueous catholyte and a Li metal anode have attracted interest owing to their exceptional energy density and high charge/discharge rate. The long‐term operation of such batteries requires that the solid electrolyte separator between the anode and aqueous solutions must be compatible with Li and stable over a wide pH range. Unfortunately, no such compound has yet been reported. In this study, an excellent stability in neutral and strongly basic solutions was observed when using the cubic Li7La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…8 indicates that some lithium still occupied the octahedral sites after the ion-exchange process. Since it was reported that ion exchange occurred in the tetragonal sites referred to the instability of the framework of garnet structure [21,32,33], the ion exchange levels in (a) area of Fig. 8 should be the safety ranges for the garnet structure, which also matched with experimental data of our study and other references [2,13,19,32,33].…”
Section: þ /H þ Ion Exchange Transition and Distribution In Cubic supporting
confidence: 69%
See 3 more Smart Citations
“…8 indicates that some lithium still occupied the octahedral sites after the ion-exchange process. Since it was reported that ion exchange occurred in the tetragonal sites referred to the instability of the framework of garnet structure [21,32,33], the ion exchange levels in (a) area of Fig. 8 should be the safety ranges for the garnet structure, which also matched with experimental data of our study and other references [2,13,19,32,33].…”
Section: þ /H þ Ion Exchange Transition and Distribution In Cubic supporting
confidence: 69%
“…The red rhombic symbols stood for the ion exchange data from Refs. [2,13,19,32,33]. The blue ones were from this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus increasing endeavors have been simulated on mass fabrication of NASICON thin films by techniques like tape‐casting . Recently, Ma et al observed that garnet‐like LLZO in neutral and strongly basic solutions can undergo a reversible Li + /H + exchange under a rate as high as 63.6% without any structural change . Such excellent behavior makes the material a very promising candidate for solid electrolyte separator in aqueous LABs.…”
Section: Electrolytes For Labsmentioning
confidence: 99%